New Advances in the Dairy Industry - Subhan Qureshi, Muhammad (IntechOpen, 2022)
This book discusses advances in the dairy industry in various parts of the world. It is divided into four sections on "Dairy Technology", "Reproductive Biotechnology", "Entrepreneurship Development", and "Sustainable Development". Chapters address such topics as regional dairy breeds, farming innovations, mineral nutrition, folliculogenesis, fertility in dairy cows, milk hygiene, and much more.